Mechanistic insight into Cp*Rh(iii)-catalyzed Lossen rearrangement vs C–N reductive elimination for the synthesis of pyridones. (12th August 2022) - Ling, Baoping; Xu, Jianqiao; Jiang, Yuan-Ye; Liu, Peng; Feng, Jin; Bi, Siwei
Abstract : A mechanism for the synthesis of rearranged and non-rearranged pyridones has been investigated using DFT calculations. Abstract : A comprehensive density functional theory study has been performed on the mechanism of Cp*Rh(iii )-catalyzed C–H activation of N -(pivaloyloxy)acrylamide with alkynyl triazene. The calculated results reveal that a concerted Lossen rearrangement/OPiv migration from N to Rh is the most favorable pathway to afford an isocyanate intermediate, where a redox-neutral process is involved without the involvement of a Rh(v )-nitrenoid species. Subsequently, the annulation of a rearranged six-membered ring intermediate is realized through a nucleophilic attack of Rh-bonded carbon on the isocyanate carbon, and this process is likely to be the rate-determining step for the entire catalytic cycle, with an overall energy barrier of 20.5 kcal mol −1 . In addition, the stepwise OPiv migration from N to Rh and C–N reductive elimination, and vice versa, are competitive to yield a non-rearranged byproduct, which experiences a Rh(iii )–Rh(v )–Rh(iii ) transformation of oxidation state.